Economia circular em empresas do Arranjo Produtivo Local (APL) têxtil da região de Americana – São Paulo: um estudo de casos múltiplos - Matsumura, Cecilia Emi Yamanaka (2023)
Population growth, climate change and growing demands on natural resources have been increasing the discussion and need to change the “extract, use and dispose” logic to a systemic approach, driven by the Circular Economy (CE) concept. This research aimed to analyze and classify EC practices at the Meso level from companies participating in the Local Productive Arrangement (APL) of the textile sector, with a regional focus, specifically the Americana region, in the State of São Paulo, developing an evaluation procedure CE practices, including actions of sharing, cooperation and management for circularity. With a qualitative, exploratory and descriptive character, the study was carried out in seven stages, configuring itself as a research of multiple cases. In the first stage, a literature review was carried out, followed by the definition of the research universe and case studies. For data collection, a questionnaire was prepared with definitions of metrics through the 9Rs structure of CE practices. For the validation of the questionnaire, a pre-test was carried out and, subsequently, interviews and technical visits were carried out in loco with defined companies to prove the CE practices indicated by them. As main results, it could be seen that the companies participating in the research presented CE knowledge and strategies at different levels, in view of the respondents’ perception. It was also identified that the companies studied are mobilizing to make the transition to the circular model within their financial and infrastructure limitations. The Recycling strategy (R8) stood out the most, since it was found that all responding companies have an adequate level of ongoing development, as this activity is still related to the linear model and, due to environmental pressure and market, has a construction of the value chain for waste from inputs used in the production process, such as cardboard and plastic packaging, for example, as well as waste generated during the process, such as shavings, scraps, etc. It was also found that, due to the fact that the companies belonging to the APL are geographically close, and have the opportunity to develop joint operations, the transition to CE is favorable for this cluster.